IMPLEMENTASI MARKET DAY SEBAGAI SARANA PEMBELAJARAN KEWIRAUSAHAAN BAGI SISWA SEKOLAH DASAR - Muniifah; Habiibah; Shella Dhiya Ulhaq; Zulfa Afifah Afra; Ferry Ferdianto (Satya Widya, 2025)
Strengthening entrepreneurial literacy from the elementary level plays a strategic role in shaping independent, creative, and socially responsible learners. This study aims to describe the implementation of the Market Day activity as a learning medium for entrepreneurial literacy at SD Negeri Pangrango. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The subjects consisted of fifth-grade students, teachers, and the school principal. The results show that Market Day provided enjoyable and contextual learning experiences, effectively improving students’ understanding of basic economic concepts such as capital, selling price, and profit. Moreover, the activity cultivated entrepreneurial character values including honesty, responsibility, teamwork, and independence. The implementation of Market Day also strengthened the dimensions of the Pancasila Student Profile, particularly cooperation, creativity, and self-reliance. This activity not only enhanced students’ economic and communication skills but also fostered positive social and moral attitudes. Therefore, Market Day can serve as an innovative, contextual, and project-based learning model that supports the development of character and entrepreneurial competence in elementary school students and aligns with the principles of the Merdeka Curriculum.